Analisis Yuridis Hak Menguasai Negara melalui Izin Pemakaian Tanah (IPT) untuk Kepentingan Umum - Galang Putra Praja; Heru Kuswanto (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Provision of land is an obligation of the State in line with the concept of the right to control land by the State. In principle, the state has the authority and also the obligation to carry out equitable designation and utilization for the community as the fulfillment of human rights. The phenomenon regarding Land Use Permits (IPT) has apparently not provided legal protection for the land users because at any time the land can be revoked by the Government because there is no strong basis for rights regarding control over Land Use Permits (IPT). The formulation of the problem used by the author is the status of land ownership rights by the State through IPT for the public interest. The research results of this writing are that the public interest is an act in the form of granting permission from authorized officials in terms of land use which is called IPT. However, it should be remembered that the use of IPT cannot be interpreted as a transfer of management rights to land or usufructuary rights to state land because the granting of a Land Use Permit is inherent in the aspect of public interest in which the provision of land is for the wider community.